Polyelectrolyte-Surfactant Mixture Effects on Bulk Properties and Antibacterial, Cytotoxic Activity of Fine Sulfur Particles - Seitzhan Turganbay; Saule Aidarova; Assem Issayeva; Zhanar Iskakbayeva; Aitugan Sabitov; Gulsinay Turganbay; Alpamys A. Babayev (Colloids and Interfaces)
Elemental sulfur, commonly known for its wide range of biological activities, has a long history of use in protecting all garden and vegetable crops from a range of pests and diseases, including powdery mildew, ascochyta blight, clubroot, plant mites, oidium, anthracnose, and scab. In the present study, a quick and environmentally friendly approach has been developed for the synthesis of sulfur nanoparticles with antibacterial activity. Fine sulfur particles (FSPs) were prepared by modifying the surface of elemental sulfur using various polyelectrolyte–surfactant mixtures (PSMs) including sodium carboxymethyl cellulose–sodium dodecylbenzene sulfonate (NaCMC-SDBS) and polyhexamethylene guanidine hydrochloride–cetyltrimethylammonium bromide (PHMG-CTAB). The FSPs were characterized by UV–visible spectrophotometry, X-ray diffraction (XRD), thermogravimetric/differential scanning calorimetry analysis (TG/DSC), and scanning electron microscopy (SEM), with the FSPs showing an almost spherical shape with an average size in the range of 150–200 nm. The antibacterial activity of the FSPs was tested against Gram-positive Staphylococcus aureus and Enterococcus faecium and Gram-negative Escherichia coli and Pseudomonas aeruginosa bacteria and one fungus (Aspergillus brasiliensis ATCC 95 16404). Based on this, it could be seen that FSPs exhibited significant antimicrobial activity against Gram-positive bacteria, i.e., S. aureus and E. faecium. The in vitro cytotoxicity of the FSPs-1 and FSPs-2 studied in normal (MeT-5A) and tumorous (MCF-7) human cell lines was assessed in the concentration range from 500 μg/mL to 0.12 mg/mL, from which it was determined as being non-cytotoxic. The received products can be considered for potential application in agriculture and medicine.